Parkinson's Disease - Douglas Gould; Lisa Haubert (MedEdPORTAL, 2012)
Abstract Parkinson's disease is a degenerative disorder of the central nervous system resulting from the death of dopamine producing cells in the substantia nigra. Parkinson's disease is the second most common neurodegenerative disorder after Alzheimer's, affecting 1% of the population over 60 years old, thus making it an essential part of any health science curriculum. The Parkinson's Disease case presentation is a short, PowerPoint containing a case-based demonstration of the differential diagnosis and treatment of Parkinson's Disease. It is intended primarily for undergraduate and graduate medical school students and residents that are preparing for or reviewing clinically-relevant neuroanatomy in relation to clinical educational experiences and endeavors. The case may be used in the lecture hall to stimulate discussion, in a small group with a qualified facilitator or for programmed individual review. Students that have completed foundational neuroanatomy training and that have been introduced to the basics of patient care, including patient interview procedures, will benefit the most from interaction with the case. The case-based neuroanatomy presentation was created for use during lecture or for small group. The framework follows basic case-based presentation methods and includes sections on: history, question, answers, differential diagnosis, treatment, and long-term outcomes. It can be adapted for use in a variety of settings to increase discussion and stimulate thought. The case was developed to be shared, so that others do not have to make the same case each time the topic is presented.